Navigator of ideas: the master Edelberto Torres-Rivas and his footprints, at one year of his departure - Morales Gamboa, Abelardo (2020)
It’s not easy to detach oneself from the subjective experiences when writing about the life and work of someone which has left its mark in our biographies. I’m refering to the life and work of Edelberto Torres Rivas, the master, and I say biographies, because that stamp marked directly on various generations of social scientists and continues to proyect itself to the present. Hereby, this account breaks with the academic protocols for placing itself on that space, by the way, necesary, between lived experience and analytical description, heaped up of ideas, but also of nourished affections.